APPLICATION OF PSEUDO-RANDOM SEQUENCE GENERATORS FOR ENERGY-EFFICIENT CONTROL OF IOT NETWORKS - Popereshnyak, S. V. (Systems and Technologies, 2025)
The paper proposes a novel method for energy-efficient management of wireless IoT networks based on the use of short pseudo-random sequences to coordinate node activity in time. Unlike traditional centralized control schemes, the proposed approach enables decentralized self-organization of the network, where each node independently determines its operation schedule using a local pseudo-random number generator. Such an organization ensures a statistically uniform distribution of active intervals, reduces the number of collisions in the radio channel, optimizes energy consumption, and increases the overall stability of communication within the network. An information model of the pseudo-random sequence generator adapted for low-power microcontrollers has been developed, as well as a local coordination mechanism that allows synchronization of node activity without a central coordinator or global time reference. The proposed state-update algorithm provides flexible adaptation to changes in network topology and traffic conditions. The paper discusses the advantages of stochastic synchronization compared to classical medium access control schemes and outlines the possibilities for integrating the method into existing IoT communication protocols. The practical value of the research lies in the ability to apply the proposed method in a wide range of sensor and monitoring systems without hardware modification. The approach can be effectively implemented in environmental and industrial monitoring networks, agricultural IoT platforms, smart city systems, and autonomous wireless infrastructures. Its application contributes to reducing energy consumption, maintaining reliable data exchange, and extending the lifetime of distributed IoT devices operating under energy constraints.